Pengembangan Karakter Warga Binaan melalui Tari Rapa’i Geleng di Lembaga Pemasyarakatan Kota Jantho Aceh Besar - Nadra Akbar Manalu; Fentisari Desti Sucipto; Tria Ocktarizka; Sartika Br Sembiring (Universitas Negeri Medan, 2020)
Dance performance plays an important role in daily life. It is not only showed on the stage but also becomes religious ceremony, therapy media, habitual fellowship, catharsis, and character development. Character development is formed by education to someone. Character education will inherent a human that has a superior character not only from cognitive aspect but also a good character in this disruption era. Rapa’i Geleng is one of traditional dance from Aceh which can be used as a development character media in Kota Jantho’s correctional institution. The purpose of this research is to develop a character for inmates through Rapa’i Geleng Dance. The method used qualitative through phsycological, religion, and pedagogic approach. Based on the result, there are significant increment in behavior of inmates through arts (Rapa’i Geleng Dance). The increment of behavior is going on the same direction as method of approach that used in this study; Physicological, Religion, and Pedagogic.